Adapting to risk and perpetuating poverty: Household's strategies for managing flood risk and water scarcity in Mexico City. Issue 66 (December 2016) - Eakin, Hallie; Lerner, Amy M.; Manuel-Navarrete, David; Hernández Aguilar, Bertha; Martínez-Canedo, Alejandra; Tellman, Beth; Charli-Joseph, Lakshmi; Fernández Álvarez, Rafael; Bojórquez-Tapia, Luis
Highlights: This paper focuses on the burden of adaptation among economically marginalized households in Mexico City and the reinforcement of poverty through chronic exposure to flooding and water scarcity. We find that the adaptation actions of households to deal with water scarcity, low quality, and flooding entail high financial and opportunity costs which contribute to cycles of poverty for households in already marginal areas. The analysis indicates that there is a need for greater attention to these tradeoffs in public policy to help ensure that adaptation does not come at the cost of more generic welfare gains, such as health and education, among the most vulnerable populations. Abstract: Adaptation is typically conceived uniquely in positive terms, however for some populations, investments in risk management can entail significant tradeoffs. Here we discuss the burden for households of coping with, and adapting to, adverse water conditions in economically marginal areas of Mexico City. We argue that households' efforts to adapt in conditions of marginality can come at the expense of households' investment in other aspects of human welfare, reinforcing poverty traps. Both economic theory and social-ecological systems analysis point to the importance of cross-scalar investments and institutional support in breaking down persistent poverty traps. Using data from twelve focus groups conducted in Mexico City, we illustrate how such cross-scale connectivity is failing as a result of lack of trust and transparency, the difficulty of collective action, and the devolution of some responsibilities for risk management from the public sector to the household level. We conclude our analysis by arguing for greater attention to these tradeoffs in public policy to help ensure that adaptation does not come at the cost of more generic welfare gains among the most vulnerable populations.